Workshop Penulisan Artikel Ilmiah Menembus Jurnal Sinta 2 - Panjaitan, Ruqiah Ganda Putri; Wahyuni, Eko Sri; Titin, Titin; Ningsih, Kurnia; Yuniarti, Anisyah; Tenriawaru, Andi Besse; Afandi, Afandi; Karmadi, Rexy Maulana Dwi (Politeknik Penerbangan Indonesia Curug, 2025)
Many students face difficulties in writing scientific articles that meet the standards of accredited journals, particularly Sinta 2, both in terms of substance and technical writing. This community service activity aims to improve students' skills in writing scientific articles in accordance with academic rules and reputable publication standards. The method used was training through a combination of material presentations and coaching clinics. The activity was carried out at the Biology Education Study Programme, Tanjungpura University, Pontianak, involving 14 students as participants. In the initial stage, students were introduced to the basic principles of scientific article writing, manuscript structure, and citation formats in accordance with accredited journal styles. Next, coaching clinics were conducted through individual guidance, where each participant received direct feedback on their article drafts. The evaluation results showed a significant improvement in the quality of the articles produced. Participants who initially had difficulty in writing titles, abstracts, and bibliographies began to show better understanding and were able to adjust their writing to the applicable standards. A comparison between the initial draft and the revised version shows noticeable improvements in both language and structure. Thus, this training and coaching clinic proved to be effective in improving students' competence in scientific writing and preparing them for publication in accredited journals.